PERANAN PENGASUH DALAM UPAYA PEMBENTUKAN KARAKTER ANAK DI PANTI ASUHAN FITRI KELURAHAN SUNGGUMINASA KECAMATAN SOMBA OPU KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This thesis discusses the Role of Caregivers in the Efforts Formation of Children's Character at the Fitri Orphanage, Sungguminasa VillageSomba Opu District, Gowa Regency. With the formulation of the problem; 1) How is the model applied by caregivers in building the character of children in the orphanage Fitri's upbringing? 2) What are the supporting and inhibiting factors of caregivers in shaping the character of children in the Fitri Orphanage? The research objectives namely to find out what model the caregivers apply at the Fitri Orphanage in the formation of children's character, to get information about what become supporting and inhibiting factors for caregivers in forming the character of the children at the Fitri Orphanage, Sungguminasa Village, Somba District Opu Gowa Regency. The type of research used in this research is research qualitative descriptive attitude using a welfare approach. The source of data from this study is the Head of the Fitri Orphanage, Caregivers of the Fitri Orphanage, Foster Children at the Fitri Orphanage, and School Teachers from children in the Fitri Orphanage. Research tools used in research are observation, interview guide, and documentation. Data analysis techniques used in this study are data reduction, data presentation, and data verification. Based on the results of data collection and processing, it can be concluded the following results: 1) the character formation model that is applied in Fitri Orphanage, namely: a) the exemplary parenting model; b) approach models affection; c) the model of the advice/counseling approach; d) formation models character with refraction; e) Character building model with reward and Punishment. 2) Supporting and inhibiting factors in character building Fitri Orphanage, namely: 1) Supporting factors: a) Orphanage environment that conducive; b) Family support; c) There is cooperation between caregivers and teachers. 2) Inhibiting factors: a) Lack of resources; b) Traumatic conditions or violence; c) Lack of trained caregivers.